Analysis Of The Customer Decision Journey For Local Fashion SMES In Optimizing Marketing Funnel Strategies Through Digital Platforms - Satria Veriansyah Wiguna (Journal of Studies in Academic, Humanities, Research, and Innovation, 2026)
This study aims to analyze the customer decision journey (CDJ) and the implementation of the marketing funnel strategy in the context of digital marketing for local fashion SMEs in Indonesia. The rapid advancement of digital technology has provided significant opportunities for SMEs to utilize various digital platforms, such as social media and e-commerce, to enhance their competitiveness and reach consumers more effectively. However, many SMEs still struggle to optimize the use of these digital platforms. Therefore, this research examines how a good understanding of the CDJ and the proper implementation of the marketing funnel strategy can influence sales conversion and customer loyalty. This study uses a quantitative approach with a descriptive research design, involving 100 respondents, consisting of local fashion SME owners and consumers who interact with them through digital platforms. The results show that a good understanding of the CDJ and the appropriate implementation of the marketing funnel significantly improve sales conversion. The findings also indicate that the consumer journey is now non-linear and influenced by various digital touchpoints, requiring a more flexible marketing strategy. Additionally, digital technologies such as recommendation systems and marketing automation tools can enhance the effectiveness of consumer interaction at each stage of the funnel. This study provides insights for SMEs to optimize their digital marketing strategies in the face of an increasingly competitive market and contributes to the literature on digital marketing for SMEs.